2013
DOI: 10.1186/1743-422x-10-354
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an envelope gene VP19 from Singapore grouper iridovirus

Abstract: BackgroundViral envelope proteins are always proposed to exert important function during virus infection and replication. Vertebrate iridoviruses are enveloped large DNA virus, which can cause great economic losses in aquaculture and ecological destruction. Although numerous iridovirus envelope proteins have been identified using bioinformatics and proteomic methods, their roles in virus infection remained largely unknown.MethodsUsing SMART and TMHMM programs, we investigated the structural characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…3A). We pre- viously demonstrated that SGIV VP19 was an envelope protein that could be specifically recognized by antibody against VP19 during SGIV infection (58). In the present study, we also assessed the percentage of SGIV-infected cells under treatment with different drugs using IFA.…”
Section: Dynamics Of Sgiv Entry Into Gs Cells Virus Infection and Entrymentioning
confidence: 73%
See 1 more Smart Citation
“…3A). We pre- viously demonstrated that SGIV VP19 was an envelope protein that could be specifically recognized by antibody against VP19 during SGIV infection (58). In the present study, we also assessed the percentage of SGIV-infected cells under treatment with different drugs using IFA.…”
Section: Dynamics Of Sgiv Entry Into Gs Cells Virus Infection and Entrymentioning
confidence: 73%
“…Citrate buffer (40 mM sodium citrate, 10 mM KCl, and 135 mM NaCl, pH 3.1) was added and left for 45 s to inactivate and remove noninternalized viruses. Cells were examined at 48 h postinfection (hpi) by IFA using anti-VP19 antibody (58).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the ectopic expressed Ec-c-Jun was translocated from nucleus to virus assembly sites. Given that virus assembly sites formed in iridovirus infection always contained numerous viral structural proteins, including membrane proteins and capsid proteins [35], we proposed that Ec-c-Jun might participate in SGIV infection via interaction with these viral proteins. During JCV infection, the transcription factors c-Jun physically and functionally interacted with JCV T-Ag and their interaction modulated JCV transcription and replication in glial cells [10].…”
Section: Discussionmentioning
confidence: 99%
“…Two late genes, SGIV ORF088 and ORF019, encode viral envelope proteins. Furthermore, rVP88 was shown to bind a 94 kDa host cell membrane protein, suggesting that VP88 might function as an attachment protein and play a role in viral entry (Huang et al 2013a ;Zhou et al 2011 ). Finally, similar approaches have been applied to ISKNV (genus Megalocytivirus ) and used to identify putative functions among a viral TRAF protein (He et al 2012a ), a viral protein that mediates formation of a mock basement membrane and provides attachment sites for lymphatic endothelial cells (Xu et al 2010 ), a viral ankyrin repeat protein that may inhibit TNFα-induced NF-κB signaling (Guo et al 2011a ), and a viral-encoded vascular endothelial growth factor (Wang et al 2008c ).…”
Section: Erv1mentioning
confidence: 99%